Future Of Bio-Waste Management in the Context of Developed Countries Legislation - Gul, Seema; Khan, Abdus Samad; Meer, Humaira (Pakistan Journal of Humanities and Social Sciences, 2022)
In The next ten years, financing and public interest will be expected to turn to Bio-waste management. Municipalities are frequently the "owners" of the fodder because they are the owners of the garbage produced on their property and are responsible for managing it. A stricter set of guidelines were added to the Waste Framework Directive in 2018 to ensure that waste streams, particularly Bio-waste, be collected separately (from December 31, 2023). In addition, it demanded raising overall recycling goals to 65 percentage points by 2035 and diverting biodegradable trash from landfills and incinerators. In order to increase their Bio-waste collection, avoidance, and recycling rates in line with EU regulations, local and regional governments should refer to the overview provided in the current policy brief on EU efforts. Policies that support a regional circular economy. Additionally, it includes several noteworthy Europe excellent practices and EU-funded projects with a high degree of dependability and adaptation to various municipal contexts. The main article focuses on the future of Bio-waste management and its legislation in developed countries. The qualitative research methodology has been applied in this article.